Extracorporeal shockwave therapy (ESWT) ameliorates healing of tibial fracture non-union unresponsive to conventional therapy. Issue 7 (July 2016) - Haffner, Nicolas; Antonic, Vlado; Smolen, Daniel; Slezak, Paul; Schaden, Wolfgang; Mittermayr, Rainer; Stojadinovic, Alexander
Abstract: Tibial non-unions are common cause of demanding revision surgeries and are associated with a significant impact on patients' quality of life and health care costs. Extracorporeal shockwave therapy (ESWT) has been shown to improve osseous healing in vitro and in vivo . The main objective of present study was to evaluate the efficacy of ESWT in healing of tibial non-unions unresponsive to previous surgical and non-surgical measures. A retrospective multivariant analysis of a prospective open, single-centre, clinical trial of tibia non-union was conducted. 56 patients with 58 eligible fractures who met the FDA criteria were included. All patients received 3000–4000 impulses of electrohydraulic shockwaves at an energy flux density of 0.4 mJ/mm 2 (−6 dB). On average patients underwent 1.9 times (±1.3 SD) surgical interventions prior to ESWT displaying the rather negatively selected cohort and its limited therapy responsiveness. In 88.5% of patients receiving ESWT complete bone healing was observed after six months irrespective of underlying pathology. The multivariant analysis showed that time of application is important for therapy success. Patients achieving healing received ESWT earlier: mean number of days between last surgical intervention and ESWT (healed – 355.1 days ± 167.4 SD vs. not healed – 836.7 days ± 383.0 SD; p  < 0.0001). ESWT proved to be a safe, effective and non-invasive treatment modality in tibial non-unions recalcitrant to standard therapies. The procedure is well tolerated, time-saving, lacking side effects, with potential to significantly decrease health care costs. Thus, in our view, ESWT should be considered the treatment of first choice in established tibial non-unions.